The Role of Digital Technologies in Enhancing Efficiency in the Cocoa Supply Chain: A Systematic Review - Akbar, Rahmad; Cahyani, Annisa; Priyana, Winda; Rahmat, Hayatul Khairul (Journal of Current Research in Management, Policy, and Social Studies, 2024)
The global cocoa industry faces increasing pressure to improve efficiency, transparency, and sustainability across its supply chain. Fragmented production networks, dependence on smallholder farmers, post-harvest losses, inconsistent quality, and price volatility remain persistent challenges in major producing countries such as Côte d’Ivoire, Ghana, Indonesia, and Nigeria. Recent advances in digital technologies—including Internet of Things (IoT), blockchain, mobile-based decision support systems, cloud-enabled traceability platforms, artificial intelligence, and geospatial analytics—offer promising avenues to address these systemic inefficiencies. This study presents a systematic literature review of peer-reviewed international journal publications from 2015 to 2024 to examine how digital technologies contribute to improved performance across cocoa supply chain stages, from farm-level production to global marketing. Searches were conducted in Scopus and Web of Science following PRISMA guidelines. A total of 84 high-quality articles met the inclusion criteria for full-text analysis. The review reveals that digital technologies enhance efficiency in four main areas: production optimization, post-harvest quality control, supply chain traceability, and market access. IoT-based monitoring systems improve yield prediction, soil management, and pest detection while reducing input misuse. Blockchain solutions increase transparency, reduce fraud, and support sustainability certification, addressing long-standing concerns about child labor and deforestation. Mobile platforms facilitate farmer training, credit access, and timely price information, reducing transaction asymmetry. Artificial intelligence and big data analytics support strategic planning, climate resilience, and risk forecasting. Despite these advances, barriers such as digital literacy, infrastructural gaps, institutional fragmentation, and cost constraints remain significant. This review concludes that digital transformation is essential for a more inclusive, resilient, and sustainable cocoa supply chain, but its success requires integrated governance, cross-sector collaboration, and enabling policies in producing countries.